Electroluminescent properties of Tb-doped carbon-enriched silicon oxide - Tiagulskyi, S.I.; Nazarov, A.N.; Gordienk, S.O.; Vasin, A.V.; Rusavsky, A.V.; Nazarova, T.M.; Gomeniuk, Yu.V.; Rudko, G.V.; Lysenko, V.S.; Rebohle, L.; Voelskow, M.; Skorupa, W.; et al. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
An electroluminescent device utilizing a heterostructure of amorphous terbium
doped carbon-rich SiOx (a - SiOx : C : Tb) on silicon has been developed. The
a - SiOx : C : Tb active layer was formed by RF magnetron sputtering of
a - SiO₁₋x : Cx : H(:Tb) film followed by high-temperature oxidation. It was shown that,
depending on the polarity of the applied voltage, the electroluminescence is either green
or white, which can be attributed to different mechanisms of current transport through the
oxide film – space charge limited bipolar double injection current for green
electroluminescence and trap assisted tunneling or Fowler-Nordheim tunneling for white
electroluminescence.